BATASAN WAKTU PERKAWINAN DALAM PERKARA ISBAT NIKAH PADA SIDANG KELILING DI PENGADILAN AGAMA CIANJUR - Muwahid, Fahmi; Ramdhani, Riyan (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2020)
Isbat nikah is one of the products of the Religious Court in the form of the determination of the marriage of a husband and wife that has been carried out in accordance with Islamic provisions. However, in the Cianjur Religious Court there are special rules regarding circuit courts in marital isbat cases, namely the year of marriage for the maximum marriage isbat in 2010, above 2010 must be registered at the Cianjur Religious Court office. This study departs from a rule that has been enacted but there are no additional rules regarding the time limit of marriage in marriage isbat cases in a circuit court. As stated in Perma No 1 of 2015 which only regulates the mechanism of the implementation of an integrated isbat trial. While the rule of law remains based on existing rules. It is stated in Article 11 paragraph (9) which states: The hearing in the Integrated Service is conducted in accordance with the procedural law and the applicable provisions. By using the descriptive analysis method, the research is first, the background of the marital time limit in marriage isbat cases which are settled in a circuit court in the Cianjur Religious Court. Second, the process of conducting a trial around isbat nikah with a time limit in the Cianjur Religious Court is no different from the process of conducting a trial around a isbat nikah case. The three rules made by the chairman of the Religious Court do not contradict the rules that already exist in the Compilation of Islamic Law (KHI) or in the request No. 1 of 2015 concerning Integrated Service Mechanisms.